Expression profile of miR-17/92 cluster is predictive of treatment response in rectal cancer - Kral, Jan; Korenkova, Vlasta; Novosadova, Vendula; Langerova, Lucie; Schneiderova, Michaela; Liska, Vaclav; Levy, Miroslav; Veskrnova, Veronika; Spicak, Julius; Opattova, Alena; Jiraskova, Katerina; Vymetalkova, Veronika; et al. (Carcinogenesis, 2018)
MicroRNA (miRNA) profiling represents a promising source of cancer-related biomarkers. miRNA signatures are specific for each cancer type and subgroups of patients with diverse treatment sensitivity. Yet this miRNA potential has not been satisfactorily explored in rectal cancer (RC). The aim of the study was to identify the specific miRNA signature with clinical and therapeutic relevance for RC. Expressions of 2555 miRNA were examined in 20 pairs of rectal tumors and matched non-malignant tissues by 3D-Gene Toray microarray. Candidate miRNAs were validated in an independent cohort of 100 paired rectal tissues and in whole plasma and exosomes of 100 RC patients. To study the association of miRNA profile with therapeutic outcomes, plasma samples were taken repeatedly over a time period of 1 year reflecting thus patients' treatment responses. Finally, the most prominent miRNAs were investigated in vitro for their involvement in cell growth. We identified RC-specific miRNA signature that distinguishes responders from non-responders to adjuvant chemotherapy. A predominant part of identified miRNAs was represented by the members of miR-17/92 cluster. Upregulation of miRNA-17, -18a, -18b, -19a, -19b, -20a, -20b and -106a in tumor was associated with higher risk of tumor relapse and their overexpression in RC cell lines stimulated cellular proliferation. Examination of these miRNAs in plasma exosomes showed that their levels differed between RC patients and healthy controls and correlated with patient's treatment response. miRNAs from miR-17/92 cluster represent a non-invasive biomarker to predict posttreatment prognosis in RC patients.
Keywords: regulace genové exprese u nádorů; Humans; MicroRNAs; Biomarkers, Tumor; Antineoplastic Agents; výsledek terapie; lidé; proliferace buněk; nádory rekta; nádorové biomarkery; Rectal Neoplasms; Cell Proliferation; Treatment Outcome; stanovení celkové genové exprese; nádorové buněčné linie; protinádorové látky; mikro RNA; Cell Line, Tumor; Gene Expression Profiling; Gene Expression Regulation, Neoplastic